Tornei-me budista sem querer : o budismo presente nas obras de Richard Wagner - Ceistutis, Alexandre Freitas (2014)
This work has contributed to substantiate and systematize the use of the concept of Buddhism (and some of its features) and closeness that Wagner having with this religion, whether by his writings, or even byhis Operas, great relevance and based on the readings fulfilled by the authors of this composer s philosophy, religion, and mythology among others and his life history. The work was fed by primary literature sources (Wagner s writings and his wife), as well as comprehensive secondary literature particular to the topic. It was chosen to do a discursive and comparative analysis of sources to reach the ultimate goals